Two-dimensional crystallization of a histidine-tagged protein on monolayers of fluidity-enhanced Ni2+-chelating lipids - Courty, S; Lebeau, L; Martel, L; Lenne, P; Balavoine, F; Dischert, W; Konovalov, O; Mioskowski, C; Legrand, J; Venien-Bryan, C (2002)
Protein two-dimensional (2D) crystallization on lipid monolayers is a powerful method for structure determination. This method has been extended using the specific and strong interaction between histidine residues (of an overexpressed protein) and Ni2+ ions tethered at the headgroup of synthetic lipids. Understanding and then improving the process of adsorption and crystallization of proteins on a lipid monolayer are prerequisites for the production of large and well-ordered crystals of any soluble or membrane His-tagged proteins. These large high-quality arrays are necessary for structural studies at high resolution. We have investigated the steps of adsorption and 2D crystallization of His-HunR using three different lipids: (i) 2-(bis-carboxymethyl-amino)-6-[2-(1,3-di-O-oleyl-glyceroxy)-acetyl-amino] hexanoic acid nickel- (II) (Ni-NTA-DOGA), which has been previously used, and two specifically designed Ni2+-chelating lipids, (ii) Ni-NTA-BB, which has two branched (B) alkyl chains and (iii) Ni-NTA-BF, a nonsymmetrical lipid with one branched (B) and one fluorinated (F) chain. These three lipids, when spread at the air-water interface, exhibit various fluidity properties. The adsorption and crystallization process have been monitored in situ and in real time using a variety of complementary techniques such as ellipsometry, shear rigidity measurements of the monolayer, and Brewster angle microscopy, and we have also developed X-ray reflectivity analysis to investigate the evolution of the electron density profile of the lipid-protein monolayer. Electron microscopy observations of the protein-lipid layers were also performed. We have found that the fluidity of the lipid monolayer has a marked influence on the rates of protein adsorption and crystallization of His-HupR. When Ni-NTA-BB is used to form the monolayer, it accelerates the process of protein adsorption and the protein crystallization is three times faster than when Ni-NTA-DOGA is used.